High-purity low-gas chromium powder for sputtering target material and preparation method of high-purity low-gas chromium powder

Through the two-stage hydrogen degassing, low-temperature crushing and magnetic separation process, the problems of uneven purity and particle size of chromium powder were solved, and high-purity, low-gas chromium powder was prepared, which is suitable for sputtering targets and improves the sputtering coating performance and production efficiency.

CN120734338APending Publication Date: 2025-10-03GRIKIN ADVANCED MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510628155.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing technologies make it difficult to prepare chromium powder with high purity, high particle size uniformity, and high stability, resulting in poor sputtering coating performance, high crushing costs, and excessively high impurity element content.

Method used

A two-stage hydrogen degassing, low-temperature crushing and magnetic separation process is adopted. The electrolytic chromium sheets are degassed in a hydrogen furnace, combined with liquid nitrogen embrittlement and high-energy magnetic separation to produce high-purity low-gas chromium powder with a purity of ≥99.99%, a particle size of ≤50μm, an oxygen content of ≤50ppm, a carbon content of ≤30ppm, and a sulfur content of ≤30ppm.

Benefits of technology

It effectively reduces the gas impurity content in the chromium powder, improves the crushing efficiency, ensures the purity and particle size of the chromium powder, and realizes high-stability and low-cost industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120734338A_ABST
    Figure CN120734338A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of powder metallurgy materials and preparation of the powder metallurgy materials, and discloses high-purity low-gas chromium powder for sputtering target materials and a preparation method of the high-purity low-gas chromium powder for the sputtering target materials. The preparation method mainly comprises the following steps that (1) electrolytic chromium sheets with the purity larger than or equal to 99.99% are adopted, and a high-purity low-gas chromium sheet with gas still enriched in part of the area is prepared through one-section stepped high-temperature hydrogen degassing; 2) performing two-stage uniform low-temperature hydrogen degassing on the high-purity low-gas electrolytic chromium sheet to prepare a high-uniformity high-purity low-gas chromium sheet; and (3) the high-uniformity, high-purity and low-gas chromium sheets are placed into a low-temperature disc mill to be smashed, and then high-purity and low-gas chromium powder with the particle size smaller than or equal to 50 micrometers is obtained through magnetic separation. The purity of the obtained high-purity low-gas chromium powder is larger than or equal to 99.99%, the particle size is smaller than or equal to 50 microns, the oxygen content is smaller than or equal to 50 ppm, the carbon content is smaller than or equal to 30 ppm, the sulfur content is smaller than or equal to 30 ppm, and the use requirement of a high-purity low-gas chromium sputtering target material can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of powder metallurgy materials and preparation thereof, and in particular relates to a high-purity low-gas chromium powder for sputtering targets and a preparation method thereof. Background Art

[0002] Chromium targets are widely used in flat panel displays and semiconductors due to their high melting point and excellent oxidation resistance. High-purity chromium targets are key materials for masks in these fields. With the continuous development of integrated circuit technology nodes, the wavelength of the exposure light source for the mask continues to decrease. The preparation of high-density, high-composition uniformity, high-purity, low-gas chromium targets plays a key role in the mask coating process. Therefore, the purity of the high-purity chromium powder required to prepare high-purity chromium targets must reach above 99.99%, with an oxygen content of ≤50ppm, a carbon content of ≤30ppm, and a sulfur content of ≤30ppm. However, the purity of chromium powder currently produced domestically is ≤99.95%, with an oxygen content of ≤150ppm, a carbon content of ≤100ppm, and a sulfur content of ≤30ppm.

[0003] The chromium powder prepared by the existing process has low purity and high impurity content such as Fe and O. The main problems include the following: (1) the electrolytic chromium sheet is not fully degassed and purified, and the content of gaseous impurities such as O and S in it is still high, which affects the sputtering coating performance of the subsequent target material; (2) the high-purity low-gas chromium sheet is brittle and ductile. It is not subjected to liquid nitrogen embrittlement treatment before crushing, which makes it difficult to continue crushing after being crushed to 500μm, reducing its crushing rate and target particle size recovery rate, increasing crushing time and increasing crushing cost; (3) the high-purity low-gas chromium sheet crushing process and the selection of crushing equipment lining are inappropriate, which reduces its crushing rate and target particle size recovery rate, introduces metal impurities such as Fe and Ni and gaseous impurities such as O, C, and S, and greatly reduces the purity of chromium powder; (4) due to the limitation of chromium target grain size and relative density, the effect of large-particle chromium powder after molding is poor, and the particle size of chromium powder needs to be reduced. However, the purity, particle size, and impurity content of Fe and O are the main factors affecting the coating performance of high-purity chromium target. Therefore, there is an urgent need to provide a method for preparing chromium powder with high purity, small particle size and low gas element content for sputtering target material. Summary of the Invention

[0004] In response to the problems existing in the prior art, the present invention discloses a method for preparing high-purity, low-gas chromium powder for sputtering targets. The chromium powder has a purity of ≥99.99%, a particle size of ≤50μm, an oxygen content of ≤50ppm, a carbon content of ≤30ppm, and a sulfur content of ≤30ppm, and realizes the industrialization of continuous production.

[0005] In response to the above problems, this patent provides a method for preparing high-purity low-gas chromium powder for high-purity sputtering targets, the steps of which are as follows:

[0006] (1) Degassing the electrolytic chromium sheet with hydrogen to obtain a high-purity, low-gas chromium sheet (i.e., a pretreated chromium sheet);

[0007] (2) Crush the high-purity low-gas chromium flakes at low temperature to obtain low-gas chromium powder (i.e., primary chromium powder) with a particle size of ≤50 μm;

[0008] (3) Magnetic separation is performed on the low-gas coarse chromium powder to obtain high-purity low-gas chromium powder (i.e., finished chromium powder) with a particle size of ≤50 μm.

[0009] In some preferred embodiments, in step (1), the chromium sheet is an electrolytic chromium sheet with a purity of ≥99.99%;

[0010] In some preferred embodiments, in step (1), the length of the chromium sheet is 10 to 30 mm;

[0011] In some preferred embodiments, in step (1), the carbon content of the chromium sheet is ≤30 ppm.

[0012] In some preferred embodiments, in step (1), a hydrogen furnace is used to degas the electrolytic chromium sheet. The inner lining of the hydrogen furnace is preferably made of molybdenum to prevent the introduction of other impurities during the degassing process. In addition, the vacuum degree of the furnace body should be better than 5×10 -3 Pa.

[0013] In some preferred embodiments, in the step (1), the electrolytic chromium sheet is subjected to hydrogen degassing treatment using a hydrogen atmosphere. The hydrogen is introduced from the lower part of the container containing the electrolytic chromium sheet and flows out from the upper part of the container containing the electrolytic chromium sheet; preferably, the purification treatment is carried out in a horizontal vacuum hydrogen furnace, and the hydrogen flow direction is bottom-in and top-out; due to the low density of hydrogen, this bottom-in and top-out method is more conducive to the smooth penetration of hydrogen through all the original electrolytic chromium sheets. Preferably, the electrolytic chromium sheets are stacked, and there are gaps between the upper and lower, left and right adjacent chromium sheets to facilitate the circulation of hydrogen and the removal of gaseous impurity elements such as O and S; if the length of the electrolytic chromium sheet is too long, it is not conducive to the circulation of hydrogen; if the length of the electrolytic chromium sheet is too short, it is not conducive to collection.

[0014] In some preferred embodiments, in step (1), the stage degassing includes 1 to 5 stages, preferably two, three, four or five stages; more preferably two stages;

[0015] In some preferred embodiments, in step (1), the degassing temperature of the stage degassing is controlled at 20 to 2000°C;

[0016] In some preferred embodiments, in step (1), the staged degassing includes staged high-temperature degassing and / or uniform low-temperature deep degassing; in some more preferred embodiments, in step (1), the two are combined for degassing;

[0017] In some preferred embodiments, in step (1), the temperature of the staged high-temperature degassing is 20 to 1600° C.;

[0018] In some preferred embodiments, in step (1), the temperature of the uniform low-temperature deep degassing is 20 to 1200°C;

[0019] In some preferred embodiments, in step (1), the electrolytic chromium sheet is subjected to a multi-stage hydrogen degassing treatment using a hydrogen atmosphere.

[0020] In some more preferred embodiments, a two-stage degassing treatment is adopted; the first stage of hydrogen degassing treatment is a staged high-temperature degassing: 1) room temperature to 400-800°C, the treatment time is 1-3 hours, and the flowing hydrogen pressure is 4000-10000Pa; 2) heating to 800-1200°C, the treatment time is 2-4 hours, and the flowing hydrogen pressure is 6000-12000Pa; 3) continuing to heat to 1200-1600°C, the treatment time is 6-8 hours, and the flowing hydrogen pressure is 8000-14000Pa, to obtain high-purity low-gas chromium sheets with gas still enriched in some areas.

[0021] In some more preferred embodiments, the second stage of hydrogen degassing treatment is uniform low-temperature deep degassing, from room temperature to 800-1200°C, the treatment time is 4-6 hours, and the flowing hydrogen pressure is 8000-14000Pa, to obtain highly uniform, high-purity, low-gas chromium sheets.

[0022] In some preferred embodiments, in step (2), the pulverizing device is a disc mill, mainly comprising a pulverizing disc, a liquid nitrogen pipeline, etc., wherein the pulverizing disc is provided with blades. The high-purity, low-gas coarse chromium powder is subjected to low-temperature treatment by injecting liquid nitrogen into the freezing tube, so that the high-purity, low-gas coarse chromium powder is brittle and easily pulverized at low temperature. In addition, the pulverizing disc is driven by a motor to rotate, and in conjunction with the inner gear ring of the inner wall of the crushing chamber, the high-purity, low-gas coarse chromium powder and the pulverizing disc, and the high-purity, low-gas coarse chromium powder and the high-purity, low-gas coarse chromium powder are repeatedly impacted and collided with each other, thereby achieving a pulverizing effect.

[0023] In some preferred embodiments, in step (2), the inner lining of the disc mill is preferably made of stainless steel to facilitate removal of magnetic impurities such as Fe and Ni introduced during the subsequent magnetic separation process. Furthermore, the rotational speed is preferably 800 to 1500 rad / min. The single pulverization time is 2 to 6 hours.

[0024] In some preferred embodiments, in step (2), liquid nitrogen is introduced into the disc mill crushing chamber as an embrittlement agent and protective gas for the high-purity, low-gas coarse chromium powder to prevent the introduction of gaseous impurities such as O. Specifically, before the high-purity, low-gas chromium flakes are crushed, they need to be soaked in liquid nitrogen, and liquid nitrogen is always introduced into the crushing chamber.

[0025] In some preferred embodiments, in step (3), the magnetic separation equipment is a high-energy magnetic separator, which mainly includes a crushing chamber and an upper conveyor belt and a lower conveyor belt therein. A magnetic roller is provided at the lower end of the upper conveyor belt, and a pressure roller structure is provided at both ends of the roller shaft. The pressure roller structure presses down the lower conveyor belt to form a concave arc-shaped magnetic separation area. In addition, a plurality of top pressure rollers are provided on the inner side of the concave portion of the lower conveyor belt, and a plurality of swing hammers are provided on the top pressure rollers to continuously strike the inner side of the lower conveyor belt during centrifugal rotation, thereby vibrating the chromium powder in the concave arc-shaped magnetic separation area. The magnetic separator can fully disperse the chromium powder to be sorted, so that the magnetic roller can fully absorb the magnetic substance in the chromium powder, and has high working efficiency.

[0026] In some preferred embodiments, in step (3), during the magnetic separation process, the high-purity low-gas chromium powder exists in an argon inert atmosphere without contact with the atmosphere or oxygen, and the purity of the argon medium is better than 99.9999%.

[0027] In some preferred embodiments, in step (3), the induced magnetic field of the high-energy magnetic separator is 20,000 Gs to 30,000 Gs.

[0028] In addition, the present application also provides a high-purity, low-gas chromium powder obtained by the preparation method, wherein the purity of the chromium powder is ≥99.99%, the particle size is ≤50μm, the oxygen content is ≤50ppm, the carbon content is ≤30ppm, and the sulfur content is ≤30ppm.

[0029] In a third aspect, the present application also provides an application of the high-purity low-gas chromium powder in a sputtering target.

[0030] The beneficial effects of this application are at least:

[0031] (1) Low gas content: This application uses a two-stage hydrogen degassing process to produce high-purity, low-gas chromium flakes, minimizing the content of gaseous elements such as O and S present in the electrolytic chromium flakes. Furthermore, the pulverization and magnetic separation processes are performed under the protection of an inert gas such as argon and nitrogen, preventing the addition of gaseous elements. The resulting high-purity chromium powder has an oxygen content of ≤50ppm and a sulfur content of ≤30ppm.

[0032] (2) Small particle size: Based on the low-temperature brittleness of high-purity low-gas chromium flakes, liquid nitrogen is used as a low-temperature embrittlement agent to reduce the difficulty of crushing high-purity low-gas chromium flakes and improve crushing efficiency. In addition, by adding a magnetic separation process after crushing, Fe and Ni introduced during the crushing process are effectively removed, and high-purity low-gas chromium powder with a particle size of ≤50μm is produced.

[0033] (3) High stability: The present application prepares high-purity chromium powder through a two-stage hydrogen degassing purification, mechanical crushing, and magnetic separation process. The quality is stable, and the content of impurity elements such as Fe and O will hardly increase. The equipment is simple and the cost is low, which can be industrialized. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a flow chart of the method for preparing high-purity, low-gas chromium powder involved in the patent of this invention;

[0035] Figure 2 This is the morphology of the high-purity, low-gas chromium powder designed for this patent. DETAILED DESCRIPTION

[0036] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation cases and comparative cases. Figure 1 The present invention is further described with specific embodiments, but is not intended to limit the scope of protection of the present invention.

[0037] The inventive mechanism of this invention is as follows: electrolytic chromium flakes with a purity of ≥99.99% are used as raw material, and high-purity, low-gas chromium flakes are first purified through a two-stage hydrogen degassing process. The high-purity, low-gas chromium flakes are then cryogenically crushed using a disc mill, and magnetic separation is performed to obtain high-purity, low-gas chromium powder ≤50μm. This avoids the problem of impurities introduced during the preparation of high-purity, low-gas chromium powder ≤50μm. The resulting high-purity, low-gas chromium powder has high purity, low content of impurities such as Fe and O, and a small particle size. The resulting target material has high density and excellent compositional uniformity.

[0038] Example 1

[0039] 1. Hydrogen degassing treatment is performed on electrolytic chromium sheets with a purity of ≥99.99% and a length of 10-30 mm. The electrolytic chromium sheet raw materials are placed in a hydrogen furnace for hydrogen degassing. The first stage is staged high-temperature degassing: 1) room temperature to 400°C, treatment time is 1 hour, and the flowing hydrogen pressure is 4KPa; 2) heating to 800°C, treatment time is 2 hours, and the flowing hydrogen pressure is 6KPa; 3) continuing to heat to 1200°C, treatment time is 6 hours, and the flowing hydrogen pressure is 8KPa, to obtain high-purity, low-gas chromium sheets with gas still enriched in some areas. The second stage is uniform low-temperature deep degassing, room temperature to 800°C, treatment time is 4 hours, and the flowing hydrogen pressure is 8KPa, to obtain high-uniformity, high-purity, low-gas chromium sheets.

[0040] 2. The high-purity, low-gas chromium flakes are crushed using a disc mill, preferably lined with stainless steel. Liquid nitrogen is used to soak the high-purity, low-gas chromium flakes before crushing, and the liquid nitrogen is introduced during the crushing process. The crushing time is 2 hours, and the final product is a low-gas chromium powder ≤50μm.

[0041] 3. Magnetic separation is performed on the low-gas chromium powder ≤50μm. The magnetic separation equipment is a high-energy magnetic separator with an induction magnetic field of 20KGs. Finally, high-purity low-gas chromium powder ≤50μm is obtained. The morphology of the prepared high-purity low-gas chromium powder is shown in the figure below. Figure 2 shown.

[0042] Example 2

[0043] High-purity, low-gas chromium powder was prepared according to the degassing, purification, pulverization, and magnetic separation steps of Example 1, except that the first stage involved staged high-temperature degassing: 1) from room temperature to 600°C, for a treatment time of 2 hours, and a flowing hydrogen pressure of 7 kPa; 2) the temperature was raised to 1000°C, for a treatment time of 3 hours, and a flowing hydrogen pressure of 9 kPa; 3) the temperature was further raised to 1400°C, for a treatment time of 7 hours, and a flowing hydrogen pressure of 11 kPa. The second stage involved uniform, low-temperature, deep degassing, from room temperature to 1000°C, for a treatment time of 5 hours, and a flowing hydrogen pressure of 11 kPa. The magnetic separation induction magnetic field was 25 kgs. The purity, particle size, oxygen content, carbon content, sulfur content, iron content, and nickel content of the resulting high-purity, low-gas chromium powder are listed in Appendix 2.

[0044] Example 3

[0045] High-purity, low-gas chromium powder was prepared according to the degassing, purification, pulverization, and magnetic separation steps of Example 1, except that the first stage involved staged high-temperature degassing: 1) from room temperature to 800°C, for 3 hours, with a flowing hydrogen pressure of 10 kPa; 2) the temperature was raised to 1200°C, for 4 hours, with a flowing hydrogen pressure of 12 kPa; and 3) the temperature was further raised to 1600°C, for 8 hours, with a flowing hydrogen pressure of 14 kPa. The second stage involved uniform, low-temperature deep degassing, from room temperature to 1200°C, for 6 hours, with a flowing hydrogen pressure of 14 kPa. The magnetic separation induction magnetic field was 30 kgs. The purity, particle size, oxygen content, carbon content, sulfur content, iron content, and nickel content of the resulting high-purity, low-gas chromium powder are listed in Appendix 2.

[0046] Comparative Example 1

[0047] High-purity, low-gas chromium powder was prepared according to the degassing, purification, pulverization, and magnetic separation steps described in Example 1, with the following differences: the first stage involved staged high-temperature degassing: 1) from room temperature to 1200°C, for 4 hours, with a flowing hydrogen pressure of 12 kPa; and 2) the temperature was raised to 1600°C, for 11 hours, with a flowing hydrogen pressure of 14 kPa. The second stage involved uniform, low-temperature deep degassing, from room temperature to 1200°C, for 6 hours, with a flowing hydrogen pressure of 14 kPa. The magnetic separation induction magnetic field was 30 kgs. The purity, particle size, oxygen content, carbon content, sulfur content, iron content, and nickel content of the resulting high-purity, low-gas chromium powder are listed in Appendix 2.

[0048] Comparative Example 2

[0049] High-purity, low-gas chromium powder was prepared according to the degassing, purification, pulverization, and magnetic separation steps described in Example 1. The differences were that the first stage involved uniform high-temperature degassing, from room temperature to 1600°C for 15 hours, with a flowing hydrogen pressure of 14 kPa. The second stage involved uniform low-temperature deep degassing, from room temperature to 1200°C for 6 hours, with a flowing hydrogen pressure of 14 kPa. The magnetic separation induction magnetic field was 30 kgs. The purity, particle size, oxygen content, carbon content, sulfur content, iron content, and nickel content of the resulting high-purity, low-gas chromium powder are listed in Table 2.

[0050] Comparative Example 3

[0051] High-purity, low-gas chromium powder was prepared according to the degassing, purification, pulverization, and magnetic separation steps of Example 1, except that a single-stage, uniform low-temperature degassing process was used: from room temperature to 800°C, for 21 hours, and with a flowing hydrogen pressure of 14 kPa. The magnetic separation induction magnetic field was 30 kgs. The purity, particle size, oxygen content, carbon content, sulfur content, iron content, and nickel content of the resulting high-purity, low-gas chromium powder are listed in Appendix 2.

[0052] Comparative Example 4

[0053] High-purity, low-gas chromium powder was prepared according to the degassing, purification, pulverization, and magnetic separation steps of Example 1, except that a single-stage, uniform low-temperature degassing process was used: from room temperature to 1200°C, for 21 hours, and with a flowing hydrogen pressure of 14 kPa. The magnetic separation induction magnetic field was 30 kgs. The purity, particle size, oxygen content, carbon content, sulfur content, iron content, and nickel content of the resulting high-purity, low-gas chromium powder are listed in Appendix 2.

[0054] Comparative Example 5

[0055] High-purity, low-gas chromium powder was prepared according to the degassing, purification, pulverization, and magnetic separation steps of Example 1, except that a single-stage, uniform low-temperature degassing process was used: from room temperature to 1600°C, for 21 hours, and with a flowing hydrogen pressure of 14 kPa. The magnetic separation induction magnetic field was 30 kgs. The purity, particle size, oxygen content, carbon content, sulfur content, iron content, and nickel content of the resulting high-purity, low-gas chromium powder are listed in Table 2.

[0056] Comparative Example 6

[0057] High-purity, low-gas chromium powder was prepared according to the degassing, purification, pulverization, and magnetic separation steps of Example 1, except that the first stage was a staged high-temperature degassing process: 1) from room temperature to 800°C, the treatment time was 3 hours, and the flowing hydrogen pressure was 10 kPa; 2) the temperature was raised to 1200°C, the treatment time was 4 hours, and the flowing hydrogen pressure was 12 kPa; 3) the temperature was further raised to 1600°C, the treatment time was 8 hours, and the flowing hydrogen pressure was 14 kPa. The second stage was a uniform low-temperature deep degassing process, from room temperature to 1200°C, the treatment time was 6 hours, and the flowing hydrogen pressure was 14 kPa. The magnetic separation induction magnetic field was 0 kgs. The purity, particle size, oxygen content, carbon content, sulfur content, iron content, and nickel content of the resulting high-purity, low-gas chromium powder are listed in Appendix 2.

[0058] Table 1 Main manufacturing process and properties of high-purity low-gas chromium powder in Example

[0059]

[0060]

[0061] Table 2 Main properties of high-purity chromium powder in examples and comparative cases

[0062]

[0063] From the results of Examples 1 to 3 above, it can be seen that in the first stage (referred to as the first stage), the low temperature is 400-800°C, the low temperature time is 1-3 hours, and the low temperature pressure is 4-10 kPa; the medium temperature is 800-1200°C, the medium temperature time is 2-4 hours, and the medium temperature pressure is 6-12 kPa; the high temperature is 1200-1600°C, the high temperature time is 6-8 hours, and the high temperature pressure is 8-14 kPa. The temperature of the second stage (referred to as the second stage) is 800-1200°C, the second stage time is 4-6 hours, and the second stage pressure is 8-14 kPa. In addition, the material is embrittled with liquid nitrogen during the pulverization process and then subjected to magnetic separation to remove impurities. The resulting high-purity, low-gas chromium powder can achieve a purity of ≥99.99%, a particle size of ≤50μm, an oxygen content of ≤50ppm, a carbon content of ≤30ppm, and a sulfur content of ≤30ppm. The process involves a low-temperature stage of 800°C, a low-temperature duration of 3 hours, and a low-temperature pressure of 10kPa; a medium-temperature stage of 1200°C, a medium-temperature duration of 4 hours, and a medium-temperature pressure of 12kPa; a high-temperature stage of 1600°C, a high-temperature duration of 8 hours, and a high-temperature pressure of 14kPa. The results are even better when the second stage is 1200°C, a second stage duration of 6 hours, a second stage pressure of 14000Pa, and an induced magnetic field of 30kgs.

[0064] The results of Examples 1-3 and Comparative Examples 1-2 demonstrate that the two-stage hydrogen degassing, low-temperature liquid nitrogen pulverization, and post-pulverization magnetic separation process disclosed in this application effectively controls the introduction of impurities such as Fe and O during the pulverization process, resolving the incompatibility issue between chromium powder particle size and impurity content, and efficiently producing high-purity, low-gassing, fine chromium powder for sputtering targets. However, compared to Examples 1-3, the amount of hydrogen used in Comparative Examples 1-2 was greater.

[0065] The results of Examples 1-3 and Comparative Examples 1-2 above demonstrate that the two-stage hydrogen degassing, low-temperature liquid nitrogen pulverization, and post-pulverization magnetic separation process disclosed in this application effectively controls the introduction of impurities such as Fe and O during the pulverization process, resolving the incompatibility issue between chromium powder particle size and impurity content, and efficiently producing high-purity, low-gas, fine chromium powder for sputtering targets. However, compared to Examples 1-3, the amount of hydrogen used in Comparative Examples 1-2 was greater. Furthermore, under these conditions, grain growth occurred in the high-purity, low-gas chromium flakes, increasing the difficulty of subsequent pulverization.

[0066] From the results of Examples 1 to 3 and Comparative Examples 3 to 5 above, it can be seen that the two-stage hydrogen degassing disclosed in this application can effectively control the impurity content of O and S during the pulverization process compared to the one-stage hydrogen degassing.

[0067] From the results of Examples 1 to 3 and Comparative Example 6 above, it can be seen that the addition of a magnetic separation process after pulverization of the high-purity, low-gas chromium flakes disclosed in this application can effectively control the impurity content of Fe and Ni during the pulverization process.

[0068] The above description of the disclosed embodiments is intended to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is intended to conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing high-purity low-gas chromium powder for sputtering targets, characterized in that: The steps include: (1) Degassing: The electrolytic chromium sheet is placed in a hydrogen furnace and degassed in stages using hydrogen to obtain a pretreated chromium sheet; The stage degassing includes 1 to 5 stages, preferably 2 stages; The degassing temperature of the degassing stage is controlled at 20-2000°C; The staged degassing includes staged high-temperature degassing and / or uniform low-temperature deep degassing; The temperature of the staged high-temperature degassing is 20 to 1600°C; The temperature of the uniform low-temperature deep degassing is 20 to 1200°C; (2) Crushing: Using a disc mill to crush the high-purity low-gas chromium flakes to obtain primary chromium powder; The pulverization speed is 800-1500 rad / min, and the single pulverization time is 2-6 hours; The particle size of the primary chromium powder is ≤50 μm; (3) Magnetic separation: Use a high-energy magnetic separator to magnetically separate the low-gas chromium powder to obtain finished chromium powder; The induced magnetic field during the magnetic separation process is controlled to be 20000Gs-30000Gs; The finished chromium powder has a purity of ≥99.99%, a particle size of ≤50 μm, an oxygen content of ≤50 ppm, a carbon content of ≤30 ppm, and a sulfur content of ≤30 ppm.

2. The method for preparing high-purity low-gas chromium powder for sputtering targets according to claim 1, characterized in that: In the step (1), the purity of the electrolytic chromium sheet is ≥99.99%; and / or Particle size is 10 to 30 mm; and / or Carbon content ≤30ppm.

3. The method for preparing high-purity low-gas chromium powder for sputtering targets according to claim 1, characterized in that: In the step (1), the stage degassing includes a first stage and a second stage; Preferably, the first stage is staged high-temperature degassing: a) room temperature to 400-800°C, treatment time is 1-3 hours, and the flowing hydrogen pressure is 4000-10000Pa; b) heating to 800-1200°C, treatment time is 2-4 hours, and the flowing hydrogen pressure is 6000-12000Pa; c) continuing to heat to 1200-1600°C, treatment time is 6-8 hours, and the flowing hydrogen pressure is 8000-14000Pa; Preferably, the second stage is uniform low-temperature deep degassing, from room temperature to 800-1200°C, with a processing time of 4-6 hours and a flowing hydrogen pressure of 8000-14000Pa.

4. The method for preparing high-purity low-gas chromium powder for sputtering targets according to claim 1, characterized in that: The inner lining of the hydrogen furnace is molybdenum metal, and the vacuum degree of the furnace body is not less than 5×10 -3 Pa.

5. The method for preparing high-purity low-gas chromium powder for sputtering targets according to claim 1 or 4, characterized in that: The hydrogen furnace is a horizontal vacuum hydrogen furnace. Preferably, the hydrogen flows in from the bottom and out from the top. Preferably, the electrolytic chromium sheets are stacked, with a gap between each two adjacent electrolytic chromium sheets, and hydrogen flows through the gap.

6. The method for preparing high-purity low-gas chromium powder for sputtering targets according to claim 1, characterized in that: Before the pulverization in step (2), the environment needs to be soaked in liquid nitrogen, and the environment is kept filled with liquid nitrogen during the pulverization process.

7. The method for preparing high-purity low-gas chromium powder for sputtering targets according to claim 1 or 6, characterized in that: The inner lining of the disc mill in step (2) is made of stainless steel as the inner cavity lining plate.

8. The method for preparing high-purity low-gas chromium powder for sputtering targets according to claim 1, characterized in that: During the magnetic separation in step (3), the chromium powder exists in an argon inert atmosphere and does not come into contact with the atmosphere or oxygen. The purity of the argon medium is better than 99.9999%.

9. A high-purity, low-gas chromium powder obtained by the preparation method according to any one of claims 1 to 8, wherein the chromium powder has a purity of ≥99.99%, a particle size of ≤50 μm, an oxygen content of ≤50 ppm, a carbon content of ≤30 ppm, and a sulfur content of ≤30 ppm.

10. Use of the high-purity low-gas chromium powder according to claim 9 in sputtering targets.